A comparison between the effects of swaddled and conventional bathing methods on some behavioral responses in premature infants - Maryam Paran; Mitra Edraki; Sedigheh Montaseri; Mostajab Razavi Nejad (Mashhad University of Medical Sciences, 2016)
Background: The newborn's first bath, performed in Neonatal Intensive Care Units (NICU), is believed to be a stressful situation, especially for the premature infants. As a developmental care approach, swaddle bathing is a low-stress bathing method for vulnerable preterm neonates. Given the limited number of the studies examining this bathing method, the present study was conducted with the aim of comparing the effects of swaddle and conventional bathing methods on some behavioral responses in premature infants. Methods: This study was a randomized clinical trial conducted on 50 premature neonates admitted to NICU. The neonates, who met the inclusion criteria, were randomly assigned into experimental and control groups. The infants in the experimental group received swaddle bathing and those in the control group were given conventional bathing. To record the behavioral responses, the infants' faces were filmed in close-up during the bathing. The data were analyzed, using Chi-squared test, independent samples t-test, and Mann-Whitney U test. Results: The results demonstrated that the occurrence rates of such behaviors as facial grimace (P